Humans in a Dish: The Potential of Organoids in Modeling Immunity and Infectious Diseases - Iakobachvili, Nino; Peters, Peter J. (Frontiers in Microbiology, 2017)
For many decades, human infectious diseases have been studied in immortalized cell lines, isolated primary cells from blood and a range of animal hosts. This research has been of fundamental importance in advancing our understanding of host and pathogen responses but remains limited by the absence of multicellular context and inherent differences in animal immune systems that result in altered immune responses. Recent developments in stem cell biology have led to the in vitro growth of organoids that faithfully recapitulate a variety of human tissues including lung, intestine and brain amongst many others. Organoids are derived from human stem cells and retain the genomic background, cellular organization and functionality of their tissue of origin. Thus they have been widely used to characterize stem cell development, numerous cancers and genetic diseases. We believe organoid technology can be harnessed to study host-pathogen interactions resulting in a more physiologically relevant model that yields more predictive data of human infectious diseases than current systems. Here, we highlight recent work and discuss the potential of human stem cell-derived organoids in studying infectious diseases and immunity.